Osobowościowe uwarunkowania procesu emancypacji osób z niepełnosprawnością wzrokową - Gładyszewska-Cylulko, Joanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2016)
The purpose of the study was to find out the relationship between personality factors and tendency to emancipation. The author focuses on the most important problems of personality of persons with visual disabilities. She wonders why do certain factors of personality encourage the process while others slow it down. The process of emancipation is complex and long-lasting but very significant not only from the perspective of people with visual disabilities, but also for all the people in a community that respect diversity.